2018
DOI: 10.1002/hfm.20730
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modeling of office environment quality, sick building syndrome, and musculoskeletal complaints on aggregate satisfaction of office workers

Abstract: This study aims to analyze the effects of office environment quality (OEQ), sick building syndrome (SBS), and musculoskeletal complaints on aggregate office satisfaction level using the structural equation. A questionnaire survey targeting 483 office workers of 18 public agencies was conducted and surveyed on workers’ characteristics (gender, age, work experience, work hours, and computer time of day), OEQ satisfaction level (temperature and humidity, lighting, noise, and air quality), SBS frequency (eye, nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Safety climate is associated with safety behaviors on the job, worker’s characteristics, working conditions, safety management system and organizational factors (Auyong et al, 2016; Champoux and Brun, 2003; Mullan et al, 2015; Nordlöf et al, 2015; Sørensen et al, 2007; Sutalaksana et al, 2016; Zohar, 2010). Some studies have been conducted to analyze a causal relation between safety-related factors using a structural equation model (Kim et al, 2017; Shin et al, 2018; Snyder et al, 2011; Stave et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Safety climate is associated with safety behaviors on the job, worker’s characteristics, working conditions, safety management system and organizational factors (Auyong et al, 2016; Champoux and Brun, 2003; Mullan et al, 2015; Nordlöf et al, 2015; Sørensen et al, 2007; Sutalaksana et al, 2016; Zohar, 2010). Some studies have been conducted to analyze a causal relation between safety-related factors using a structural equation model (Kim et al, 2017; Shin et al, 2018; Snyder et al, 2011; Stave et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The sample frame consists of 76 valid questionnaires comprising 30 bank staffers and 46 worshipers. Recent studies [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] have documented the negative effects of sick building syndrome on human health across climes. The survey instrument was administered by hand and consists of four parts.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Respondents tend to complain about headaches and eye irritation after working a day at the office [29,36]. Another study in the office setting also said nose and throat irritation are the most common SBS symptom [34]. However, a study shows that nose irritation was the least reported SBS symptom at the office [38].…”
Section: Sbs At the Officementioning
confidence: 99%